2015
DOI: 10.1111/jphp.12434
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lung-delivered in-situ forming controlled release formulations

Abstract: In-situ forming controlled release hydrogels represent a viable approach for inhalative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It is worth noting that at body temperature the G ʹʹ value of GEL1 became obviously lower than that of GEL2. It is known that the gelation capability of poloxamer solutions depends closely on the polymer concentration22, 23, 24. Our result indicated that both the two formulations had adequate anti-dilution capacity, assuring that they could form hydrogels after administration in the vagina even after dilution by vaginal fluid.
Figure 3Effect of dilution on the gelation process of the hydrogel formulations (5 mL) with 0.5 mL (A and B) or 0.75 mL (C and D) simulated vaginal fluid.
…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that at body temperature the G ʹʹ value of GEL1 became obviously lower than that of GEL2. It is known that the gelation capability of poloxamer solutions depends closely on the polymer concentration22, 23, 24. Our result indicated that both the two formulations had adequate anti-dilution capacity, assuring that they could form hydrogels after administration in the vagina even after dilution by vaginal fluid.
Figure 3Effect of dilution on the gelation process of the hydrogel formulations (5 mL) with 0.5 mL (A and B) or 0.75 mL (C and D) simulated vaginal fluid.
…”
Section: Resultsmentioning
confidence: 99%
“…Only a few studies have been carried out on developing non-oral sustained release SDF dosage forms using polymers, for example, lung-delivered, controlled release formulations of SDF with poloxamer-407 (P-407) [ 8 ] or a vaginal controlled release suppository of SDF containing EVAC 210 polymer [ 9 ]. In addition, some SDF formulations were prepared with polymers, such as SDF nano-dispersion inhalers incorporating poloxamer-188 (P-188) [ 10 ], SDF solid lipid nanoparticles formulated with gelucire 44/14 [ 11 ], SDF spray-dried microparticle inhalers formed by using sodium carboxymethylcellulose, sodium alginate, and sodium hyaluronate [ 12 ], SDF-loaded polymeric microparticles based on poly(lactide-co-glycolide) [ 13 ], and an SDF microemulsion-loaded hydrogel [ 14 ].…”
Section: Introductionmentioning
confidence: 99%